2019
DOI: 10.2196/13008
|View full text |Cite
|
Sign up to set email alerts
|

Completeness of Electronic Dental Records in a Student Clinic: Retrospective Analysis

Abstract: Background A well-designed, adequately documented, and properly maintained patient record is an important tool for quality assurance and care continuity. Good clinical documentation skills are supposed to be a fundamental part of dental student training. Objective The goal of this study was to assess the completeness of electronic patient records in a student clinic. Methods Completeness of patient records was assessed using comparative revie… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 47 publications
1
8
0
Order By: Relevance
“…Data from Medicaid claims, private insurance claims, emergency department records, and many other primary data sources have been used in oral health data analysis studies across the globe . Recent studies identified potential limitations of using EHR data generated solely by dental schools as they may represent a biased patient sample . Similarly, administrative and claims records such as Medicaid data represent a very valuable resource use of which requires understanding of its strengths and limitations .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Data from Medicaid claims, private insurance claims, emergency department records, and many other primary data sources have been used in oral health data analysis studies across the globe . Recent studies identified potential limitations of using EHR data generated solely by dental schools as they may represent a biased patient sample . Similarly, administrative and claims records such as Medicaid data represent a very valuable resource use of which requires understanding of its strengths and limitations .…”
Section: Discussionmentioning
confidence: 99%
“…33,37,43 Recent studies identified potential limitations of using EHR data generated solely by dental schools as they may represent a biased patient sample. 59 Similarly, administrative and claims records such as Medicaid data represent a very valuable resource use of which requires understanding of its strengths and limitations. 60 Future research should capitalize on growing availability of integrated comprehensive data sets representing all facets of oral health.…”
Section: Where To Gather Datamentioning
confidence: 99%
See 1 more Smart Citation
“…16 A few studies have evaluated the completeness and correctness of EDR data in academic institutions to identify gaps and improve dental students' training for patient care documentation. [20][21][22] These studies indicate the need to establish a systematic process to evaluate the data quality of EDR-derived datasets and to promote fidelity and reproducibility of secondary data analysis.…”
Section: Background and Significancementioning
confidence: 99%
“…Good dental records do not imply exceptional dental services, however, they are of great importance as they allow monitoring the quality of services provided to patients over some time (8).…”
Section: Introductionmentioning
confidence: 99%